Production objectives and selection criterions of three endemic ruminant breeds in The Gambia and Senegal - García, L.; Ignacio P. (Swedish University of Agricultural Sciences, 2013)
Livestock plays a major role in the livelihood of poor rural communities, being the source of tangible and intangible benefits. The objective of this study was to analyse the production objectives and selection criteria for cattle (N’Dama) and small ruminants (Djallonké sheep and West African Dwarf goat) in The Gambia and Senegal. A Participatory Rural Appraisal (PRA) survey was conducted in 18 villages in both countries. A total of 412 livestock owners and contract herders participated in the survey. The results showed that benefits such as manure production, income, savings and insurance, were the most important reasons for keeping ruminants. Furthermore, cows were important for milk sale and domestic milk consumption, and bulls were kept for draught. Intangible benefits, such as ceremonial and dowry were some of the main reasons for keeping small ruminants. In The Gambia body size was the most important selection criterion for all species. Trypanosomiasis resistance was essential when selecting cattle. Other important selection criterion traits were milk yield in cows, growth in bulls, and fertility and disease resistance in goats. In Senegal, cattle selection was based mainly on morphological characteristics, i.e. body size, conformation and growth. Trypanosomiasis resistance in cattle was rated lower than in The Gambia. In both countries, body size, fertility and growth were the main traits when selecting small ruminants. Generally, most of the farmer’s production objectives were in harmony with the selection criteria. However, a number of differences were noted. In The Gambia sheep were selected for milk yield, but this was not an essential production objective. In addition, milk yield was an important selection criterion for cows but not for bulls. Inbreeding was the least important selection criterion in both countries. This divergence in production objectives with selection criteria, and the negative effects of inbreeding need to be addressed in breeding programmes in order to conserve, improve and sustainably utilise these three endemic ruminant species.